Scalp metastasis from occult primary breast carcinoma: A case report and review of the literature - N. Alizadeh, MD; H. Mirpour, MD; S.Z. Azimi, MD (Wolters Kluwer, 2018)
Background: Isolated distant cutaneous metastasis of breast carcinoma is uncommon. Furthermore, isolated metastasis of the scalp seems to be very rare in breast cancer. Case presentation: A 44-year-old woman was referred to our dermatology department with concerns of a firm, painless, immobile, hardened, skin-colored mass fixed to the underlying tissues. The lesion measured 2 to 3 cm on the scalp frontalis without regional or distant lymphadenopathy. The patient had a history of benign right breast biopsy test results.Immunohistochemistry test results were positive for cytokeratin (AE1/AE3), cytokeratin 7, chromogranin, estrogen receptor, and gross cystic disease fluid protein-15; group PR/HER2 were both weakly positive. Cytokeratin 20, thyroid-lung transcription factor, S100 protein, vimentin and thyroglobulin were all negative. Pathology test results showed adenocarcinoma that was consistent with breast primary. Conclusion: Although cutaneous metastasis of the chest wall due to breast carcinoma is a common condition, scalp metastasis as the first sign of occult breast cancer is an extremely rare condition. We describe an isolated scalp metastasis as the initial presentation of breast cancer in a young woman in this report, which highlights that health care providers should be alert to the possibility that atypical soft tissue masses may represent a neoplasm. Further consideration of the scalp lesions among healthy looking patients is recommended.